решите неравенство 3/(2^(2-x^2)-1)^2-4/(2^(2-x^2)-1)+1>=0
3/(2^(2 - x²) -1)² - 4/(2^(2- x²) -1) + 1 ≥ 0 ;
замена : t = 2^(2-x²) -1
3 / t² - 4 / t +1 ≥ 0 ;
(t² - 4t +3) / t² ≥ 0
для квадратного трехчлена t² - 4t +3 t₁=1 корень: 1² - 4*1+3 = 1- 4+3 =0.
t₂ =3/t₁=3/1=1 (или t₂ =4 -1=3)
* * * наконец можно и решить уравнение t² - 4t +3=0 * * *
(t² - 4t +3) / t² ≥ 0 ⇔ (t -1)(t - 3) / t² ≥ 0 .
+ + - +
(0) [1] [ 3]
* * * совокупность неравенств [ { t ≤ 1 ; t ≠0 . { t ≥ 3 * * *
a)
{ 2^(2-x²) -1 ≤ 1 ; 2^(2-x²) -1 ≠ 0 .⇔ { 2^(2-x²) ≤ 2 ; 2^(2-x²) ≠ 1 . ⇔
{ 2^(2-x²) ≤ 2¹ ; 2^(2-x²) ≠ 2⁰.⇔ {2-x² ≤ 1 ; 2 - x² ≠ 0.⇔{ x² -1 ≥ 0 ; x² ≠ 2⇔
{ (x+1)(x-1) ≥ 0 ; x ≠ ±√2 . ⇒ x∈ ( -∞ ; -√2 ) ∪ (-√2 ; -1] ∪ [1 ; √2) U (√2 ; ∞) .
b)
2^(2-x²) -1 ≥ 3 ⇔ 2^(2-x²) ≥ 4 ⇔2^(2-x²) ≥ 2² ⇔2- x² ≥ 2 ⇔ x² ≤ 0 ⇒ x=0.
ответ: x∈ ( -∞ ; -√2 ) ∪ (-√2 ; -1] ∪ { 0} ∪ [1 ; √2) U (√2 ;
Объяснение:
S = b1/(1 - q)
У нас b1 = 8, q = 0,5, S = 8/(1 - 0,5) = 16
2) Арифметическая прогрессия
a(n) = a1 + d*(n - 1)
У нас a1 = 3, d = 4, n = 10, a(10) = 3 + 4*9 = 3 + 36 = 39
3) b1 = 9, q = -1/3, S = 9/(1 - 1/3) = 9/(2/3) = 9*3/2 = 13,5
4) Сумма арифметической прогрессии
S = (a1 + a(n))*n/2
a1 = 2, n = 102-2+1 = 101, a(101) = 102
S = (2 + 102)*101/2 = 52*101 = 5252
5) a1 = -3, d = -3, n = 25, a(25) = -3 - 3*24 = -3 - 72 = -75
6) a1 = 10, d = -2, n = 10, a(10) = 10 - 2*9 = 10 - 18 = -8
S(10) = (10 - 8)*10/2 = 2*10/2 = 10